Preparation of zinc and cerium or both doped Cu2O photoelectric material via hydrothermal method. (15th January 2020) - Yuan, Binxia; Liu, Xiaobo; Cai, Xiaodong; Fang, Xinyi; Liu, Jianfeng; Wu, Maoliang; Zhu, Qunzhi
Highlights: The zinc and cerium or both doped cuprous oxide (Cu2 O) crystals were synthesized by a simple hydrothermal process. The reaction temperature was less than 80 °C. The synthetic process was very simple and non-toxicity. Abstract: In the paper, the zinc and cerium or both doped cuprous oxide (Cu2 O) crystals were successfully synthesized under low temperature by a simple hydrothermal process. The surface morphologies, structure properties, and optical properties of Cu2 O crystals were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and UV-visible absorption spectroscopy. The morphology of pure Cu2 O crystals, Zn:Cu2 O crystals, Ce:Cu2 O crystals and Zn/Ce:Cu2 O crystals evolved to irregularly cubic structure, exfoliated octahedron, were regular octahedron, and like-spherical aggregate, respectively. The doping of Cu2 O crystals not only affected the surface morphologies but also significantly influenced the optoelectronic properties. Compared with undoped cuprous oxide, the doped samples had larger optical band gaps. Finally, the aggregation and diffusion were the most important factors for the morphology evolution of Cu2 O crystal.